What ails physician review websites? A study of information needs of patients - Ghosh, Soham (My University, 2023)
Physician Review Websites (PRWs) help users select physicians by providing both structured and unstructured data on physicians and patients' experiences with physicians. In this paper, the adequacy of the available information on PRWs is investigated. An empirical study is conducted to understand the information that patients seek from PRWs through a survey instrument administered to 344 patients. A topic modelling approach is then employed on 666,551 text reviews of patients using data from a popular PRW in India to discover information available on the PRWs. Combining both approaches, it is found that 12 out of 25 topics are either unavailable or only partially available, indicating an information gap. Two topics which constitute the information gap are then utilised to conduct a full factorial experiment on 153 respondents using a Latin Square design. Experimental results demonstrate that adding relevant information improves the physician selection process. Our work contributes to the healthcare IS literature on online physician selection and the role of information availability. The results will help PRWs and hospitals decide how to restructure information on their websites and devise strategies to nudge patients to write reviews highlighting the desired information.
PUBLISHED
Keywords: Physician review websites (PRWs), Healthcare analytics, Topic modelling, Online reviews, Patient experience, Experimental design; Digital Humanities; Business Analytics